Dental microwear analysis in Gliridae (Rodentia): methodological issues and paleodiet inferences based on "Armantomys" from the Madrid Basin (Spain) - Oliver, A.; Hernández-Ballarín, V.; López-Guerrero, P.; García-Paredes, I.; Álvarez-Sierra, M.A.; Gómez Cano, A.R.; García Yelo, B.A.; Alcalde, G.M.; Peláez-Campomanes, P. (Journal of Iberian Geology, 2014)
In the present study we analyze the microwear of the species included in the lineage Armantomys aragonensis-A. tricristatus of two samples from two middle Miocene localities from the Madrid Basin (El Cañaveral and Casa Montero). The methodological part of the study compares light stereomicroscope photographs from resin casts and Environmental Scanning Electron Microscope (ESEM) photographs from original material. Furthermore two regions of the tooth crown (the most lingual part of the anteroloph, and the most lingual part of the protoloph) and two homologous regions of first and second upper molars have been analyzed. The paleoecological part includes the results of the microwear analyses of the two species included in the lineage A. aragonensis-A. tricristatus. The replacement of A. aragonensis with A. tricristatus in the Madrid Basin occurred during the Middle Miocene Climate Transition (MMCT) and is marked by a change in dental morphology. Therefore, in order to infer changes in diet associated to a shift in the environment, we checked for correlations on microwear features between the two different morphologies of the species. The two methodologies tested, ESEM on original teeth and light stereomicroscopy on resin casts, showed similar results on microwear analysis in the glirid Armantomys. Besides, both regions of the tooth crown and dental elements showed the same microwear patterns. The substitution of the species included in the lineage Armantomys aragonensis-A. tricristatus might not imply a change in diet.